ISLAM NUSANTARA: Studi Epistemologis Dan Kritis - Alma’arif, Alma’arif (Analisis: Jurnal Studi Keislaman, 2015)
Religion  and culture  are two  different  things  but  very  closely related.  The  majority  of people  are very  complicated  or quite difficult  to distinguish  the absolute  religion, and which culture becomes  an  expression  well  as  vehicle  and  relatively   it.  Of course,  the  inability  of a person  to  distinguish  lack  of clarity is causing chaos in thinking  epistemological  side, chaos in the sense  of hierarchy  where  the  value  associated  with  the  higher values  and the  lower  values,  which  is absolute  and which  are relatively.  Departing  from these  problems,  using the historical- anthropological  approaches and methods of analysis-critical then this  article  tries  to discuss about  archipelagic  Islam. The main stression is in the epistemological  analysis of archipelagic Islam. Critical analysis carried out toward archipelagic Islam is expected to map it which aims unveil what  should be retained  and that what  should  be deconstructed.  The conclusion  from this  study is the dialectics between religions that have moral and universal values with the culture and traditions  of the people of Indonesia to form a distinctive style of Indonesian Islam is commonly called archipelagic Islam. Archipelagic Islam is legitimate  from the standpoint  of epistemological.  Critical analysis  of archipelagic Islam yield maping, on which should be kept and which should be deconstructed. Among the things that should be maintained is the spirit of archipelagic  Islam tolerance  in diversities, appreciation of good  traditions  and  elasticity  in reading  of religious texts. The  things  that  should  be deconstructed  is the  doctrine  of al- Ghazali in hostile philosophy and natural  sciences and a strong guard toward myths and mystical archipelagic Islam that impede progress and civilization.